Electrochemical Behaviour of Zinc in Chloride and Acetate Solutions - Kilincceker, G.; Galip, H. (Maik Nauka/Interperiodica/Springer, 2009)
The corrosion behaviour of zinc in chloride medium was investigated in the absence as well as the presence, of acetate ions. The temperature effect was also investigated by varying the temperature in a range of 298 to 328 K, while the pH was kept constant at 8.5. Polarization resistance (R-p) and activation energy (E-a) values were determined, by means of potentiodynamic and EIS measurements. Thermodynamic properties were evaluated with the current-potential measurements. The temperature, ionic species and the parts of oxide film on anodic and cathodic processes are discussed. It was shown that zinc acetate [Zn(CH3COO)(2)] formation could provide important protection with other zinc corrosion products, against the attack of corrosive environment.
Keywords: Anodic-Dissolution; Alpha-Brass; Corrosion; Inhibition; Impedance; Electrode; Copper; Model; Iron; Sulfate